1997
DOI: 10.1046/j.1365-2729.1997.00025.x
|View full text |Cite
|
Sign up to set email alerts
|

Computer mediated tutorial support for conventional university courses

Abstract: In an effort to restore quality and flexibility to the tutorial provision on some undergraduate courses, first, second and third year psychology students at the University of Southampton have been inducted into the use of ‘skywriting’ as a medium for learning support. Email messages from students and tutors, primarily focussed on issues arising from the course content, are directed to a course list so that all participants receive them; both tutors and students may reply to these. The course tutor maintains a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 3 publications
6
40
0
Order By: Relevance
“…The findings about the quantity of participation, however, are contradictory. Some reported that females contributed more to CMC than in face to face interaction (Light, Colbourn & Light, 1997), whereas others found that females produced more messages in face to face communications than in CMC (Adrianson, 2001).…”
Section: Computer Mediated Communicationmentioning
confidence: 99%
“…The findings about the quantity of participation, however, are contradictory. Some reported that females contributed more to CMC than in face to face interaction (Light, Colbourn & Light, 1997), whereas others found that females produced more messages in face to face communications than in CMC (Adrianson, 2001).…”
Section: Computer Mediated Communicationmentioning
confidence: 99%
“…Having a more mixed group of students in terms of level of education and subject may help to overcome such complaints. However, Light et al (1997) report better results when`skywriting' was used with third year students, all studying the same specialised subject. They likened the experience to`shared commentaries'.…”
Section: The Nature Of the User Groupsmentioning
confidence: 93%
“…With an emphasis on conversation, McLoughlin and Oliver (1998) consider that learning around computers can be facilitated through collaborative learning where students interact with one another (peer interaction) and with teachers. An example of such learning might be the use of computer-based tutorials that employ e-mail as a communication tool (Light, Colbourn & Light, 1997). They have the capacity to encourage re¯ection by using conversation and collaboration as tools for helping students to adapt and reframe ideas.…”
Section: Using Learning Technologies To Facilitate Re¯ectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some students who are quiet in class increase their participation using email and electronic conferencing, needing the additional time and reflection to post either their observations or questions (DuttDoner & Powers, 2000). However, some students are more reticent and are actually put off by the public nature of electronic conferencing (Light et al, 1997). Wilson et al (1996) found that despite the growth of the Internet, many students still do not participate in electronic conferencing and other Internet uses.…”
Section: Perspectives On Technology Standards In Higher Educationmentioning
confidence: 99%